A Comparative Study of Early Maladaptive Schemas, Behavioral Problems and Self-Esteem between Single Parent and Two Parent Female Adolescents (Global Journal of Human-Social Science, 2017)
The present study aimed to investigate early maladaptive schemas, behavioral difficulties and self-esteem among female adolescents with single and two parent status in Bonab city. In this causalcomparative study, 52 students with single parent and 52 with two parent status were selected. In order to gather the data, Achenbach Youth Self-Report (YSR), Short Form of Young Schema Questionnaire (YSQSF), and Cooper Smith (CSE) Self Esteem scale were administered. Analysis of variance and t-test for independent groups were used for analyzing the data. The results showed that there was significant difference in terms of social isolation/alienation, failure, dependence/incompetence, vulnerability to harm or illness, subjugation and self-sacrifice schemas between the two groups. Additionally, the results revealed that there was a significant difference in subscales of anxious/depressed, withdrawn/depressed, social problems, attention problems, and aggressive behavior between the two groups.
Keywords: single parent; two parent; early maladaptive schema; self-esteem; behavioral difficulties and adolescents